Solvent-dependent aggregation behavior of a new Ru(ii)-polypyridyl based metallosurfactant - Mahato, Prasenjit; Saha, Sukdeb; Choudhury, Sipra; Das, Amitava (Chemical Communications, 2011)
Variation of the solvent polarity leads to the formation of vesicles and reverse vesicles of a newly synthesized amphiphilic Ru(II)-polypyridyl complex.